KONFLIK BULLYING DAN STRATEGI PENANGANANNYA DI SMP NURUL BURHAN WIDODAREN - Hikmawati, Hanifah; Lathifah, Dewi Zulfa Hikmatul (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2024)
Bullying conflicts often occur in formal school education environments and have many impacts. Bullying conflicts in schools are a serious problem that can affect students' well-being and the overall learning environment. This research is descriptive qualitative field research. Information sources in this research are categorized into two groups, namely primary data (primary data) and secondary data. Data sources were selected using a purposive sampling method, namely by directly appointing individuals who have the knowledge and expertise to provide reliable and accurate information regarding the subject matter under study. Meanwhile, data collection methods or research instruments use observation, interviews and documentation. Data analysis used in this research includes data reduction, data presentation, and drawing conclusions/verification. The results of this research, the author can limit the problem, namely, Bullying is violent behavior carried out by individuals or groups who have power over other individuals who are weaker. This research identified four types of bullying that occurred at Nurul Burhan Widodaren Middle School, namely physical, verbal, mental and cyberbullying. The teacher's role in overcoming bullying includes the role of advisor and guide, by applying a persuasive approach and character learning. Teacher strategies involve religious learning approaches, character education, and collaboration with parents to reduce bullying and increase students' social awareness. Keywords: Conflict, Bullying, Strategy, Nurul Burhan Middle School